Anterior neck and airway ultrasound procedures with emphasis on resuscitation plus video clips. (June 2020) - Breitkreutz, Raoul; Sladdin, Emily; Geuting, Markus; Schröder, Tobias C.; Lindner, Dennis; Damjanovic, Domagoj
Abstract: What can anterior neck and airway ultrasound add to the established methods in emergency airway management, including capnography? The aim of this narrative review is to review relevant methods. We describe three major categories of anterior neck and airway ultrasound exam methods in order to distinguish its applicability within a defined clinical context. We particularly describe two types of focused anterior neck ultrasound exam styles depending on the clinical scenario, post-intubation (type #1 style) and during intubation (type #2 style). Regarding both exam styles, the key message is to identify or rule out a double tract immediately, indicating an esophageal misplacement. For this finding no ventilation trial is mandatory. In case of clinical emergency scenarios, this is the major advantage in comparison to capnometry. Exam type #1 style is a very brief sonoscopy-like exam and can be performed within 10 s in an ALS-conformed way. As these stethoscope-like examinations can be integrated into the advanced life support algorithm, it is suggested that anterior neck and airway ultrasound should be part of the collection of methods of "Resuscitation Ultrasound" and training. To make it available to a wider audience, the exam techniques are visualized in video clips and available at www.yumpu.com/en/SonoABCD . Considering the evidence and limitations of anterior neck and airway ultrasound procedures in emergencies, training within scenarios or a defined clinical context is recommended. These point-of-care ultrasound methods should be readily accessible for emergency and critical care practitioners.